Uji Aktivitas Antioksidan Ekstrak Daun Temurui (Murraya koenigii L Spreng) Dengan Penentuan Kandungan Senyawa Aktif Menggunakan UPLC-MS - Afandi, Trisno; Permata, Intania; Hariyanto Hariyanto; Rahmat, Nahzim; Nainggolan, Fernando (Berkala Ilmiah Kimia Farmasi, 2024)
People have historically utilized temurui leaves to treat diabetes and diarrhoea. This study aimed to determine the temurui leaf extract's antioxidant properties. Antioxidant activity was examined on methanol, ethyl acetate, and methanol extracts of temurui leaves using the FRAP (Ferric Reducing Antioxidant Power) and DPPH (2,2-diphenyl-1-picryhydrazyl) techniques spectrophotometrically at wavelengths of 720 and 517 nm, respectively. Antioxidant activity parameters were measured based on the IC50 value. The results showed that methanol, ethyl acetate, and n-hexane extracts of temurui leaves had relatively weak antioxidant activity with IC50 values of 179,745±4,26; 189,730±15,403; and 282,244±12,297 mg/L (DPPH method) and 287,305±19,054; 344,809±63,907; 505,065±32,567 mg/L (FRAP method), respectively. Therefore, methanol extract of temurui leaves has the potential as a better antioxidant than n-hexane and ethyl acetate extracts. The UPLC-QTof-MS/MS analysis indicated that the methanol extract of these leaves consists of 13 chemicals such as phenolic, steroid, and alkaloid groups which are closely related to its antioxidant properties.   Keywords:  Murraya koenigii L spreng, Antioxidant, DPPH, FRAP, UPLC-MS